A practical approach to Events Medicine provision. Issue 8 (9th September 2016) - Smith, Susan P; Cosgrove, Joseph F; Driscoll, Peter J; Smith, Andrew; Butler, John; Goode, Peter; Waldmann, Carl; Vallis, Christopher J; Topham, Fiona; Mythen, Michael (Monty)
Abstract : In the past three decades, mass casualty incidents have occurred worldwide at multiple sporting events and other mass gatherings. Organisational safety and healthcare provision can consequently be scrutinised post-event. Within the UK, such incidents in the 1980s provided incentives to improve medical services and subsequent high profile UK-based international sporting events (London Olympics and Paralympics 2012, Glasgow Commonwealth Games 2014, Rugby World Cup 2015) added a further catalyst for developing services. Furthermore in the aftermath of the abandoned France versus Germany association football match at the Stade de France ( Paris Terrorist Attacks, November 2015) and the 2016 UK report from HM Coroner on the Hillsborough Inquest, medical cover at sporting events is being further reviewed. Doctors providing spectator cover therefore need to have an awareness of their likely roles at sporting venues. Formal guidance exists in many countries for the provision of such cover but remains generic even though Events Medicine is increasingly recognised as a necessary service. The current evidence base is limited with best practice examples often anecdotally cited by acute care specialists (eg, emergency medicine) who provide cover. This article is therefore intended to present an overview for doctors of the knowledge and skills required to treat ill and injured spectators and enable them to adequately risk-assess venues in cooperation with other health and safety providers, including preparation for a major incident. It also gives guidance on how activity can be adequately assessed and how doctors can have management roles in Events Medicine.